An observational study to assess the prevalence of cardiovascular disease in type 2 diabetes mellitus patients on treatment with oral antidiabetic drugs, at a Tertiary care hospital, in Chennai - JEYALALITHA RATHINAM; SHANMUGAM.A; ARUN MURUGAN.S; ANURADHA.C.R; PREETHI.A (International Journal of Pharma and Bio Sciences, 2018)
Cardiovascular disease remains the single greatest cause of morbidity and mortality among patients with type 2 diabetes mellitus and hyperglycemia remains a major contributor. As indicated through several trials, the various comorbid conditions and the currently available anti diabetic medications by themselves may contribute towards the complications of type 2 diabetes mellitus. This study was done to assess the prevalence of cardiovascular disorder in type 2 diabetes mellitus patients on treatment with oral anti diabetic drugs.An observational study was done by examining 503 patients with type 2 diabetes over a period of 6 months in a tertiary care hospital in Chennai. The data obtained was analyzed with respect to patients with cardiovascular disease and without cardiovascular disease. A total of 143 patients were found to be with cardiovascular disease among the 503 patients assessed. 41.25 % of patients were under metformin monotherapy while 47.55 % were on metformin and sulfonylureas, 5.59 % on metformin with voglibose and 5.59% on metformin and pioglitazone combination therapy. Aspirin, statins and ACE inhibitors were among the co prescribed drugs. The prevalence of cardiovascular disease was found to be 28%. It was a cross sectional analysis and the data obtained was not adequate to correlate the prevalence of cardiovascular disease to the intake of any specific antidiabetic medication. The traditional risk factors contributing to type 2 diabetes such as obesity, smoking, hypertension and dyslipidemia was found to be significant with a positive family history which could be the contributing factor towards development of cardiovascular disease in these patients. All these comorbid conditions in patient with type 2 diabetes, positively point towards the constellation of factors contributing to the existence of metabolic syndrome which by itself is considered as a risk factor for cardiovascular disease. A prospective large scale study can prove to be a better tool to assess the relation between the occurrence of cardiovascular disease in patients on oral antidiabetic medications.